Bifurcation of equilibrium forms of a gas column rotating with constant speed around its axis of symmetry. (December 2021) - Janczewska, Joanna; Zgorzelska, Anita
Abstract: We will be concerned with the problem of deformation of the lateral surface of a column that rotates with constant speed around its axis of symmetry. The column is filled by a gas and our goal is to investigate the deformation of the lateral surface depending on the pressure of the gas.